Kekuatan Pasar dan Stabilitas Dualisme Bank Perkreditan Rakyat Akibat Penetrasi Teknologi Finansial - Moh Najikhul Fajri (Komisi Pengawas Persaingan Usaha, 2022)
The advancement of digital access conventional rural banks (BPR) and sharia rural banks (BPRS) compete with the presence of financial technology (fintech). Fintech penetration is projected to have an impact on market forces and credit risks of rural banks. By looking at this phenomenon, this research is directed to review the influence of penetration of financial technology institutions on the existence of market power and challenges of rural banks stability. Market power is measured using a non-structural approach, namely the Lerner Index. Meanwhile, banking stability is measured using non-performing loans. This research is using dynamic panel regression: generalized method of moments over 1,266 BPR and 113 BPRS during 2013-2019. The results show that fintech has a positive effect on market strength and negatively affects the stability of BPR/S. Fintech penetration provides resilience for the market strength of conventional and sharia rural banks through collaboration between institutions. Not only that, but economic growth is found to have brought market power even higher. On the other hand, the decline in banking stability was caused by the fact that rural banks and other rural banks did not open opportunities for cooperation, thereby increasing credit risk.